Analisis Tinjuan Penggunaan Diksi Berita Pangan pada Media Online CNBC Indonesia - Adhi Kusuma; Iffan Zulkais; Abi Rabsanjani (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Diction, in this context, is understood as the selection of appropriate and appropriate words in conveying ideas, which not only affects the clarity of information, but also the style, tone, and persuasiveness of a text. This research is motivated by the importance of word choice in conveying messages to the public, especially in the realm of mass media which has a central role in shaping public perception of issue strategies, such as food security. The main objective of this study is to describe the types of diction used in CNBC Indonesia’s food news, as well as to analyze how the selection of certain words affects the meaning and persuasiveness of the message conveyed. The use of diction in CNBC Indonesia’s food news is very strategic and selective. Specific words such as "stabilization of food supply and prices" or the term "quarter" are used to emphasize the technical and specific context of a food policy. Meanwhile, general words such as "food security" and "nation and state" reflect the broad scope of the ideas conveyed, thus opening up space for more inclusive interpretation. Contradictory sentences that highlight the disagreement between the elite and farmers create narrative tension that strengthens the appeal of the message. In addition, the presence of conjunctions such as "however," "without," and "in order to" provide continuity of meaning and build cause-effect logic in the representation of information.